Magnetic-molecularly imprinted polymers in electrochemical sensors and biosensors - Marfà, J.; Pupin, R. R. [UNESP]; Sotomayor, Mpt [UNESP]; Pividori, M. I. (Springer Nature, 2021)
Magnetic particles, as well as molecularly imprinted polymers, have revolutionized separation and bioanalytical methodologies in the 1980s due to their wide range of applications. Today, biologically modified magnetic particles are used in many scientific and technological applications and are integrated in more than 50,000 diagnostic instruments for the detection of a huge range of analytes. However, the main drawback of this material is their stability and high cost. In this work, we review recent advances in the synthesis and characterization of hybrid molecularly imprinted polymers with magnetic properties, as a cheaper and robust alternative for the well-known biologically modified magnetic particles. The main advantages of these materials are, besides the magnetic properties, the possibility to be stored at room temperature without any loss in the activity. Among all the applications, this work reviews the direct detection of electroactive analytes based on the preconcentration by using magnetic-MIP integrated on magneto-actuated electrodes, including food safety, environmental monitoring, and clinical and pharmaceutical analysis. The main features of these electrochemical sensors, including their analytical performance, are summarized. This simple and rapid method will open the way to incorporate this material in different magneto-actuated devices with no need for extensive sample pretreatment and sophisticated instruments. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Biomimetic receptors; Electrochemical biosensors; Magnetic particles; Magnetic-MIPs; Molecularly imprinted polymers